Impairment reversals and stock market returns: The case of Malaysia - Shaari, Hasnah (2015)
FRS 136 Impairment of Assets requires companies to reverse impairment loss when their impaired assets are recovered. This study examines the motivation for impairment reversals.A sample of 182 Malaysian firms that report impairment reversals during the period 2006-2009 are matched by industry and size with 182 control firms.This study finds that reversing firms outperform control firms in the year of the reversal suggesting that firms in Malaysia on average reverse impairments to reflect the recovery in the value of assets. In additional analysis, this study finds that reversal reporting by Malaysian firms that are less likely to manage earnings is positively associated with stock market returns.In contrast, reporting of impairment reversal by firms with extremely high abnormal working capital accruals (an indication of earnings management) has no relation with stock valuation.